Disequilibrium δ18O values in microbial carbonates as a tracer of metabolic production of dissolved inorganic carbon. (15th February 2017) - Thaler, Caroline; Millo, Christian; Ader, Magali; Chaduteau, Carine; Guyot, François; Ménez, Bénédicte
Abstract: Carbon and oxygen stable isotope compositions of carbonates are widely used to retrieve paleoenvironmental information. However, bias may exist in such reconstructions as carbonate precipitation is often associated with biological activity. Several skeleton-forming eukaryotes have been shown to precipitate carbonates with significant offsets from isotopic equilibrium with water. Although poorly understood, the origin of these biologically-induced isotopic shifts in biogenic carbonates, commonly referred to as "vital effects", could be related to metabolic effects that may not be restricted to mineralizing eukaryotes. The aim of our study was to determine whether microbially-mediated carbonate precipitation can also produce offsets from equilibrium for oxygen isotopes. We present here δ 18 O values of calcium carbonates formed by the activity of Sporosarcina pasteurii, a carbonatogenic bacterium whose ureolytic activity produces ammonia (thus increasing pH) and dissolved inorganic carbon (DIC) that precipitates as solid carbonates in the presence of Ca 2+ . We show that the 1000 ln α CaCO 3 - H 2 O values for these bacterially-precipitated carbonates are up to 24.7‰ smaller than those expected for precipitation at isotopic equilibrium. A similar experiment run in the presence of carbonic anhydrase (an enzyme able to accelerate oxygen isotope equilibration between DIC and water) resulted in δ 18 O values of microbial carbonates in line with values expected at isotopic equilibrium with water. These results demonstrate for the first time that bacteria can induce calcium carbonate precipitation in strong oxygen isotope disequilibrium with water, similarly to what is observed for eukaryotes. This disequilibrium effect can be unambiguously ascribed to oxygen isotope disequilibrium between DIC and water inherited from the oxygen isotope composition of the ureolytically produced CO2, probably combined with a kinetic isotope effect during CO2 hydration/hydroxylation. The fact that both disequilibrium effects are triggered by the metabolic production of CO2, which is common in many microbially-mediated carbonation processes, leads us to propose that metabolically-induced offsets from isotopic equilibrium in microbial carbonates may be more common than previously considered. Therefore, precaution should be taken when using the oxygen isotope signature of microbial carbonates for diagenetic and paleoenvironmental reconstructions.